2010
DOI: 10.1007/s11661-010-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Stresses during Casting of Binary Magnesium-Aluminum Alloys

Abstract: A viscoplastic stress model is used to predict contraction forces measured during casting of two binary Mg-Al alloys. Force measurements from castings that did not hot tear, together with estimates from data found in the literature, are used to obtain the high-temperature mechanical properties needed in the stress model. In the absence of hot tearing, the simulation results show reasonably good agreement with the measurements. It is found that coherency of the semisolid mush starts at a solid fraction of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Hamdi et al [3] studied the casting process of AA6060 alloy using a finite element model ALSIM, and found the viscoplastic strain rate played an important role for the center cracks. Pokorny et al [4] used a viscoplastic stress model to simulate the stresses during the casting of binary magnesiumaluminum alloys, and the simulation results were reasonably good agreement with the measurements. Hao et al [5] developed a thermomechanical finite element model to simulate the casting of magnesium alloy AZ31, and studied the hot tearing tendency using a pressure-based criterion called Rappaz-Drezet-Gremaud (RDG).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hamdi et al [3] studied the casting process of AA6060 alloy using a finite element model ALSIM, and found the viscoplastic strain rate played an important role for the center cracks. Pokorny et al [4] used a viscoplastic stress model to simulate the stresses during the casting of binary magnesiumaluminum alloys, and the simulation results were reasonably good agreement with the measurements. Hao et al [5] developed a thermomechanical finite element model to simulate the casting of magnesium alloy AZ31, and studied the hot tearing tendency using a pressure-based criterion called Rappaz-Drezet-Gremaud (RDG).…”
Section: Introductionmentioning
confidence: 87%
“…The values for Q and s 0 are 215.82 kJ mol À1 , [8] 4 MPa, [4] respectively. The strain-rate-sensitivity coefficient m is shown in Figure 2d, drawn from the results of some researches on AZ91 alloy.…”
Section: Thermophysical and Mechanical Propertiesmentioning
confidence: 99%
“…The experimental device developed for this study can obtain the thermal load during solidification under the condition that the contraction was prevented for the two purposes: one is validating the thermal stress analysis through comparison of the analytical value of the load with the experimental one; 1,16,17) the other is determining the crack initiation temperature. 1,1820) For the latter, earlier studies 1820) have revealed that the thermal load increased with the progress in freezing under the condition that the solidification contraction was prevented.…”
Section: Experimental Devicementioning
confidence: 99%
“…Moreover, the mechanical response of the solid itself shows strain rate dependency (i.e. [8]). In-situ observations of the deformation behavior of a semi-solid Al-Cu alloy with the X-ray microtomography employed by Terzi et al [9] show that the deformation in the semi-solid is highly inhomogeneous.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The value is used for simulations in the main chapter. As also mentioned in[58], Poisson's ratio is almost independent of temperature, so a typical value 0.33 is used in this thesis. A static (reference) yield stress ζ 0 varies with temperature.…”
mentioning
confidence: 99%